2011
DOI: 10.1002/app.34823
|View full text |Cite
|
Sign up to set email alerts
|

PLA/chain‐extended PEG blends with improved ductility

Abstract: Melt blending of polylactic acid (PLA) and a chain-extended polyethylene glycol (CE-PEG) have been performed in an effort to toughen the PLA without significant loss of modulus and ultimate tensile strength. The chain-extended PEG was prepared with melt condensation of a low molecular weight PEG and 4,4 0 -methylenebis(phenylisocyanate) (MDI) for enhancement of the molecular weight of PEG. The thermal and mechanical properties, miscibility and phase morphologies of blends were investigated. By using thermal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 24 publications
2
34
0
1
Order By: Relevance
“…When compared with neat PLA, the PLA/PEG/NaCl blends with different contents of NaCl (30 and 40 wt %), the tensile strength decreased from 54.9 MPa to 22.18 MPa and 16.62 MPa, whereas the average elongation at break increased from 6.86% to 26.34% and 11.27%. This result is consistent with the prior results from Sheth et al and Park et al The mechanical properties indicate that the addition of the PEG increases the flexibility of the blends system.…”
Section: Resultssupporting
confidence: 92%
“…When compared with neat PLA, the PLA/PEG/NaCl blends with different contents of NaCl (30 and 40 wt %), the tensile strength decreased from 54.9 MPa to 22.18 MPa and 16.62 MPa, whereas the average elongation at break increased from 6.86% to 26.34% and 11.27%. This result is consistent with the prior results from Sheth et al and Park et al The mechanical properties indicate that the addition of the PEG increases the flexibility of the blends system.…”
Section: Resultssupporting
confidence: 92%
“…The brittleness does hinder its applications ranging from packaging materials to medical implants . To improve the elongation at break and impact strength, various modifier polymers (e.g., rubber or other polymers with excellent flexibility) have been widely employed to blend with PLLA . The binary blend, however, always undergoes phase separation because of weak interfacial interaction and poor miscibility between PLLA and other polymers.…”
Section: Methodsmentioning
confidence: 99%
“…[3,4] To improve the elongation at break and impact strength, various modifier polymers (e.g., rubber or other polymers with excellent flexibility) have been widely employed to blend with PLLA. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] The binary blend, however, always undergoes phase separation because of weak interfacial interaction and poor miscibility between PLLA and other polymers. Therefore, compatibilizers have been introduced to the blend system.…”
mentioning
confidence: 99%
“…Dorati et al investigated the degradation behavior of poly(ethylene glycol‐ co ‐ d , l ‐lactide) (PEG‐ d,l ‐PLA) multiblock copolymer. Park et al demonstrated that melt blend chain‐extended polyethylene glycol (CE‐PEG) with polylactic acid (PLA) could toughen the PLA matrix without significant modulus and ultimate tensile strength reduction. Moreover, as a plasticizer, many scaffolds based on PLA‐PEG block copolymer have been prepared to increase the flexibility and hydrophilicity of PLA .…”
Section: Introductionmentioning
confidence: 99%